Farmland Dispute Prevention: The Role of Land Titling, Social Capital and Household Capability - Shunran Wang; Fangping Rao; Xianlei Ma; Xiaoping Shi (Land, 2022)
Disputes over farmland constitute an important challenge for tenure security, economic growth and social stability. Land titling is a theoretically promising policy instrument that can enhance tenure security and reduce the occurrence of farmland disputes in the developing world. However, the impact of land titling on the occurrence of disputes has been found to be highly conditional. Empirical evidence on this issue has been surprisingly limited and has often lacked the consideration of a specific context. In this study, whether land titling affects the incidence of farmland disputes in the context of China is investigated, focusing particularly on the interaction between land titling and social capital and household capability. Both the probit and CLL models are applied, using household data entailing a total of 3693 samples located in rural China. The results show that (1) land titling in China reduces the incidence of farmland disputes, and that (2) the analysis based on interaction terms indicates that households who are disadvantaged in social capital and household capability are more likely to experience fewer disputes. Implications for the government and organizations are as follows: (1) the titling programme should seriously consider the current tenure arrangement. Confirmation of current tenure is recommended over the establishment of a new system to avoid possible institutional shopping and overlapping claims; and (2) land titling, if well implemented, is recommended to redress local power asymmetry and to help vulnerable groups defend their property.